The effect of supplementation with type I and type III collagen peptide and type II hydrolyzed collagen on pain, quality of life and physical function in patients with meniscopathy: a randomized, double-blind, placebo-controlled study - Ahmet Serhat Genç; Ali Kerim Yılmaz; Berna Anıl; Esra Korkmaz Salkılıç; Enes Akdemir; Berna Güzel; Ahmet Mor; Hacı Ahmet Yarar; Nizamettin Güzel; Lokman Kehribar (BMC Musculoskeletal Disorders)
Abstract Background Menisci, one of the most important anatomical structures of the knee joint, plays a role in load transfer, stability, shock absorption, prevention of articular cartilage degeneration, and proprioception. Type I collagen, the main component of the meniscus, and type II collagen fibers play an important role in the stability of the knee joint. This study aimed to evaluate the effects of Naturagen® 4 Joint product containing type I, II, and III collagen on pain, quality of life, and physical functions in patients with meniscopathy. Methods This randomized, double-blind, placebo-controlled clinical study included 32 patients (collagen = 17 and placebo = 15) with meniscopathy. Patients completed the Visual Analog Scale (VAS), Western Ontario and McMaster Universities Osteoarthrtis Index (WOMAC), Knee Injury and Osteoarthritis Outcome Score Physical Function Short Form (KOOS-PS), Oxford Knee Score (OKS), Tampa Scale for Kinesiophobia (TSK), Short Form Health Survey (SF-12), Lower Extremity Functional Scale (LEFS), Foot Function Index (FFI), proprioceptive sensation, Timed Up and Go (TUG), 6-Minute Walking Test (6MWT), The Five Repetition Sit to Stand Test (5STS), Stair Climbing Test (SCT), Berg Balance Scale (BBS) and back and leg strength tests and scales were applied. All tests were repeated before and after eight weeks of collagen supplementation. Results The study showed that eight weeks of supplementation with various collagen types had statistically significant effects on pain, quality of life, kinesiophobia, and foot function scale scores in patients with meniscopathy (p < 0.05). Similarly, eight weeks of supplementation showed a statistically significant difference in leg strength (p = 0.057), but no significant difference was found in back strength, proprioception, balance, and various functional test results (p > 0.05). Conclusions The results of the study showed that the eight-week collagen-based supplement had a positive effect on pain and quality of life levels and some functional test results in patients with meniscopathy. Longer-term studies and diversification of subject groups will help to understand better the effects of the product on meniscal tears and symptoms. Trial registration The study was retrospectively registered in the Iranian Clinical Trials Registry on 14/05/2024 with the number IRCT20240411061470N2.